Assessing the environmental impacts of furfural production in a poplar wood biorefinery: A study on the role of mannitol concentration and catalyst type - Khounani Z.; Abdul Razak N.N.; Hosseinzadeh-Bandbafha H.; Madadi M.; Sun F.; Fattah I.M.R.; Karimi K.; Gupta V.K.; Aghbashlo M.; Tabatabaei M. (Elsevier B.V., 2024)
Furfural is a versatile chemical building block derived from hemicellulose-rich lignocellulosic biomass. Considering the availability of various process routes and conditions, it is crucial to determine the most environmentally sustainable production routes and conditions for furfural production. This study evaluates the life cycle environmental impacts of furfural production in a poplar wood-based biorefinery, considering varying mannitol concentrations (015% w/w) and catalyst types (FeCl3, FeCl2, CuCl2, AlCl3, and MgCl2). An attributional cradle-to-gate life cycle assessment (LCA) framework is adopted, with a functional unit of 1 kg of furfural production. The environmental impacts of furfural production are evaluated using the IMPACT World+ method at both midpoint and endpoint levels. Based on the findings, the furfural production process utilizing an AlCl3 catalyst and a 5% w/w concentration of mannitol exhibits superior environmental performance compared to all the other conditions evaluated. Compared to the mannitol-free process, this condition can reduce up to 30.80% of all the environmental impacts of furfural production. By substituting FeCl2, FeCl3, CuCl2, and MgCl2 with AlCl3, significant savings of 64.77%, 45.06%, 78.77%, and 79.30%, respectively, in all the environmental burdens of furfural production can be achieved. The results highlight that choosing an appropriate catalyst can greatly decrease the environmental impact of furfural production. Furthermore, the use of fossil-based electricity is a significant contributor to the environmental impacts of the process. Thus, an eco-friendly approach to producing furfural involves altering the means of electricity generation. 2023 Elsevier B.V.